Impact Of Sharia-Based Product Differentiation To Encourage The Growth Of Islamic Banks In Indonesia - Syarifuddin, Syarifuddin; Pagalung, Gagaring; Kara, Muslimin; Mansyur, Alif Ilman (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2022)
The development of Islamic banks in Indonesia today can be said to be slow when compared to conventional banks. There are several challenges that cause this, such as capital problems, the development of sharia product innovations, to the inadequate quality of human resources, to limited infrastructure in sharia economic development. In this study, we will discuss one of these challenges, namely the development of sharia product innovation or called sharia product differentiation. The purpose of this study is to determine the effect of product differentiation, on people's decisions in choosing banks and products to be used and their impact on the development of Islamic banks in Indonesia. This research is descriptive research using secondary data related to the effect of product differentiation on Islamic banking. The population in this study are residents throughout Indonesia who use Islamic banks. The results of the study indicate that the variable in question, namely product differentiation, is considered important so that it has an impact on people's decisions to choose whether to use products from Islamic banks. This will automatically encourage the growth rate of Islamic banks in Indonesia.